Evaluation of readiness to commercialize research results with the IRL framework: a case study of ORC turbines in Indonesia - Utomo, Setyo Margo; Azka, Muizuddin; Budiwati, Solichah Vichy; Rahman, Abdul; Setiawan, Hari; Faisal, Faisal; Hastuti, Pudji; Ilyas, Aldrich (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Indonesia's commitment to reducing the use of fossil fuels for power generation has encouraged the exploration of biomass energy from waste materials. Organic Rankine cycle (ORC) turbine technology that converts waste into electrical energy can be an opportunity for the development of waste power plants. The developed ORC turbine has not been assessed for innovation readiness level (IRL). To address this gap, a comprehensive evaluation of the IRL and technology readiness level (TRL) of the ORC turbine is essential. This study uses qualitative and quantitative methods, combining the IRL and TRL frameworks. The results reveal that the ORC turbine market is ready, although the technology is still in the early stages of development (IRL 2). In order to achieve IRL 3 and be prepared to enter the decline stage as part of the market evolution phase, intellectual property protection, product testing, and certification must be carried out. The establishment of a product certification agency with testing facilities to ensure turbine performance is required. IRL and TRL approaches can be used to determine the stages of research activities that can be achieved by looking at the availability of resources needed at each level.